Roles, trends and challenges of neglected and underutilized species in Ghana. A review of the literature - Vernooy, Ronnie (2021)
For rural communities in Ghana, neglected and underutilized crop species (NUS) are important for nutrition, food security and income generation. However, little is known about their diversity and potential; very little has been published about NUS in Ghana. This review summarizes the main findings of a review of recent literature.